Albumin binding ligands and albumin conjugate uptake by cancer cells - Frei, Eva (Diabetology & metabolic syndrome, 2011)
The scope of this short review is to summarise the knowledge gleaned from the fate of drugs transported by albumin upon contact with the target cancer cell or cells in inflamed tissues. The authors expertise covers covalently bound drugs and their cellular uptake and release from albumin. This review therefore aims to deduce what will happen to drugs such as insulin detemir which is considered to bind non-covalently to albumin and may have a fate similar to fatty acids transported by albumin.
Gesehen am 07.03.2023